Freestanding Graphene Fabric Film for Flexible Infrared Camouflage. Issue 5 (16th December 2021) - Cui, Guang; Peng, Zhe; Chen, Xiaoyan; Cheng, Yi; Lu, Lin; Cao, Shubo; Ji, Sudong; Qu, Guoxin; Zhao, Lu; Wang, Shaokai; Wang, Shida; Li, Yizhen; et al.
Abstract: Graphene films, fabricated by chemical vapor deposition (CVD) method, have exhibited superiorities in high crystallinity, thickness controllability, and large‐scale uniformity. However, most synthesized graphene films are substrate‐dependent, and usually fragile for practical application. Herein, a freestanding graphene film is prepared based on the CVD route. By using the etchable fabric substrate, a large‐scale papyraceous freestanding graphene fabric film (FS‐GFF) is obtained. The electrical conductivity of FS‐GFF can be modulated from 50 to 2800 Ω sq −1 by tailoring the graphene layer thickness. Moreover, the FS‐GFF can be further attached to various shaped objects by a simple rewetting manipulation with negligible changes of electric conductivity. Based on the advanced fabric structure, excellent electrical property, and high infrared emissivity, the FS‐GFF is thus assembled into a flexible device with tunable infrared emissivity, which can achieve the adaptive camouflage ability in complicated backgrounds. This work provides an infusive insight into the fabrication of large‐scale freestanding graphene fabric films, while promoting the exploration on the flexible infrared camouflage textiles. Abstract : A freestanding graphene film is reported by etching graphene‐coated substrate with fabric structure. Moreover, the large‐scale papyraceous freestanding graphene fabric film (FS‐GFF) can be further attached to various shaped substrates and showing a superior electrical conductivity. Meanwhile, the FS‐GFF based infrared camouflage flexible textile device exhibits superior infrared camouflage performance.